Rapid Determination of Meat Moisture Content Using Radio-Frequency Dielectric Measurement - Jianxu Wang (IEEE, 2018)
Moisture content is an important meat quality trait. The fast and low-cost detection for the moisture content of meat or meat products is continuously concerned by researchers. At radio frequencies, the dielectric properties of meat are strongly affected by its moisture content. Therefore, we proposed a fast detection method for moisture content of pork meat by using a quarter-wavelength transmission line at 150 MHz and an interdigital electrode-based probe. In this paper, we simulated the electric field distribution around the probe. To verify the performance of the designed device, relevant calibrations, and tests were conducted. The measurement results of moisture content obtained by our device and the network analyzer at 150 MHz were compared. The results indicate that our device can distinguish the change of moisture content between 72% and 80% in the minced pork meat. This method has considerable potential as a means for rapid determination of meat moisture content.